Dystopia, utopia – or somewhere in between? Healthy City Design 2019, London, 14–15 October. Issue 1 (2nd January 2020) - Cooper, Katy
ABSTRACT: A review of the 3rd Healthy City Design International Congress: ' Designing for Utopia or Dystopia: People and Planetary Health at a Crossroads' (held in London in October 2019) and a look forward to the next Congress in the context of 2020 as a pivotal year for health and the environment.